CHARACTER–IDEA UNITY IN ERNEST HEMINGWAY’S NOW I LAY ME (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article provides a theoretically grounded and psychologically oriented analysis of Ernest Hemingway’s short story “Now I Lay Me”, focusing on the problem of character–idea unity. Drawing on the principles of literary psychology, modern narratology, and Hemingway’s iceberg theory, the study argues that the central idea of the story is not articulated through explicit authorial commentary but is embodied in the psychological structure of the protagonist, Nick Adams. The analysis demonstrates that trauma, memory, and controlled consciousness function as key mechanisms through which character becomes the primary bearer of meaning. The article contributes to contemporary Hemingway studies by highlighting the inseparability of character formation and ideological content in minimalist prose.